Anesthetic management of patients with sepsis/septic shock - Carsetti, Andrea; Vitali, Eva; Pesaresi, Lucia; Antolini, Riccardo; Casarotta, Erika; Damiani, Elisa; Adrario, Erica; Donati, Abele (Frontiers in Medicine, 2023)
Sepsis is defined as life-threatening organ dysfunction caused by a dysregulated host response to infection, while septic shock is a subset of sepsis with persistent hypotension requiring vasopressors to maintain a mean arterial pressure (MAP) of ≥65 mmHg and having a serum lactate level of >2 mmol/L, despite adequate volume resuscitation. Sepsis and septic shock are medical emergencies and time-dependent diseases with a high mortality rate for which early identification, early antibiotic therapy, and early source control are paramount for patient outcomes. The patient may require surgical intervention or an invasive procedure aiming to control the source of infection, and the anesthesiologist has a pivotal role in all phases of patient management. During the preoperative assessment, patients should be aware of all possible organ dysfunctions, and the severity of the disease combined with the patient's physiological reserve should be carefully assessed. All possible efforts should be made to optimize conditions before surgery, especially from a hemodynamic point of view. Anesthetic agents may worsen the hemodynamics of shock patients, and the anesthesiologist must know the properties of each anesthetic agent. All possible efforts should be made to maintain organ perfusion supporting hemodynamics with fluids, vasoactive agents, and inotropes if required.